El aprendizaje infantil en el desarrollo de la motricidad gruesa de los niños de 4 a 5 años del Centro Educativo Intercultural Bilingüe “Abraham Lincoln” durante el período lectivo 2019-2020 - Conlago Chulli, Sonia Consuelo (2020)
Child learning has many implications in the future life of the child and conducting research focused on seeking methodological strategies that strengthen this process is vital, for this reason the objective was to determine how child learning influences through recreational activities In the low development of the gross motor skills of children from 4 to 5 years of the Abraham Lincoln Bilingual Intercultural Educational Center, to carry out the study an investigation was carried out with a quantitative approach with descriptive scope and of the applied type of field, for being a small sample universe the population and the sample coincide, being constituted by 15 boys and girls from 4 to 5 years of age and a teacher in charge of the children. To gather information, an interview was applied that allowed to know the current situation of the school regarding the promotion of gross motor skills in the learning process and the Ozer Motor Scale Test before and after executing the technical proposal based on recreational activities for the development of gross motor skills, the results obtained showed that no techniques were applied to the motor development of children, likewise the numerical data were analyzed by means of the student t test for comparison of paired means using the IBM SPSS software as a tool, throwing as As a result, the development of the motor level in children was greater after the application of dynamic activities in the classroom and that these results had a reliability of more than 95%, which confirmed the alternative hypothesis. That is, that recreational activities do influence the development of gross motor skills